Nobiletin Inhibits Non-Small-Cell Lung Cancer by Inactivating WNT/β-Catenin Signaling through Downregulating miR-15-5p. (30th December 2021) - Han, Sang Hyup; Han, Jeong Hee; Chun, Wan Joo; Lee, Sang Soo; Kim, Hae Sung; Lee, Jin Won
Abstract : Background . Nobiletin is a natural compound with anticancer activity; however, the mechanism is not clear. Methods . The inhibitory effect of nobiletin on non-small-cell lung cancer (NSCLC) cells was examined using soft agar, Transwell, and apoptosis analyses. Cancer stemness was measured by sphere assay. Genes and miRNAs regulated by nobiletin were identified by whole-genome sequencing. Protein levels were detected by western blot and immunofluorescence assays. Results . Nobiletin significantly inhibited NSCLC cell colony formation and sphere formation and induced apoptosis. Nobiletin upregulated negative regulators of WNT/ β -catenin signaling, including NKD1, AXIN2, and WIF1, while it inhibited the expression of β -catenin and its downstream genes, including c-Myc, c-Jun, and cyclin D1. Furthermore, we identified that GN inhibits miR-15-5p expression in NSCLC cells and that NKD1, AXIN2, and WIF1 are the target genes of miR-15-5p. Conclusions . Nobiletin has a strong inhibitory effect on NSCLC, and nobiletin plays an anticancer role by inhibiting miR-15-5p/ β -catenin signaling in NSCLC.